Nanofiber scaffold based on polylactic acid-polycaprolactone for anterior cruciate ligament injury - Aminatun; Rifqha Huriah; Dyah Hikmawati; Hadi, Sofijan; Tahta Amrillah; Che Abdullah, Che Azurahanim (Multidisciplinary Digital Publishing Institute, 2022)
Anterior Cruciate Ligament (ACL) injuries are becoming more prevalent in athletes. Anterior Cruciatum Ligament Reconstruction (ACLR) surgery was used to treat ACL injuries and resulted in a recurrence rate of 94% due to the biomechanically repaired tissue being weaker than the original tissue. As a result, biodegradable artificial ligaments must be developed that can withstand mechanical stress during neoligament formation and stabilize the ACL. The purpose of this study is to determine the effect of composition variations in polylactic acid (PLA) and polycaprolactone (PCL) used as ACL nanofiber scaffolds on ultimate tensile strength (UTS) and modulus of elasticity, fiber diameter, cytotoxicity level, and degradation level, as well as the PLA-PCL concentration that provides the best value as an ACL scaffold. Electrospinning was used to fabricate the nanofiber scaffold with the following PLA-PCL compositions: A (100:0), B (85:15), C (80:20), D (70:30), and E (0:100) (wt%). The functional group test revealed no new peaks in any of the samples, and the ester group could be identified in the C-O bond at wave numbers 1300–1100 cm−1 and in the C=O bond at wave numbers 1750–1730 cm−1. The average fiber diameter, as determined by SEM morphology, is between 1000 and 2000 nm. The unbraided sample had a UTS range of 1.578–4.387 MPa and an elastic modulus range of 8.351–141.901 MPa, respectively, whereas the braided sample had a range of 0.879–1.863 MPa and 2.739–4.746 MPa. The higher the PCL composition, the lower the percentage of viable cells and the faster the sample degrades. All samples had a cell viability percentage greater than 60%, and samples C, D, and E had a complete degradation period greater than six months. The ideal scaffold, Sample C, was composed of PLA-PCL 80:20 (wt%), had an average fiber diameter of 827 ± 271 nm, a living cell percentage of 97.416 ± 5.079, and a degradation time of approximately 219 days.